Fishery and stock dynamics of ribbonfish Trichiurus lepturus (Linnaeus, 1758) in the Indian Exclusive Economic Zone: Ribbonfish stock dynamics - Shubhadeep Ghosh; Prathiba Rohit; A. Margaret Muthurathinam; K. M. Rajesh; Mohammed Koya; C. Anulekshmi; Ajay D. Nakhwa; S. Surya; H. M. Manas; Subal K. Roul; P. Abdul Azeez; R. Vinoth Kumar (Indian Journal of Fisheries, 2024)
The fishery and stock dynamics of Trichiurus lepturus (Linnaeus, 1758) were studied in the Indian Exclusive Economic Zone (EEZ) for the period 2014-2019. The average annual landing was 2,09,285 t and varied from 1,77,259 to 2,39,355 t. Trawl nets were the major gear, contributing more than 85% with an average annual catch rate of 4.56 kg h-1. The annual catch rate decreased over the years from 5.40 to 3.85 kg h-1. Landings (23,155-40,354 t) and catch rates (4.24-8.67 kg h-1) were highest during the post-monsoon months (September-December). Around 63% of the landings (1,32,072 t) were from the north-west coast, with Gujarat alone contributing three-fourth (98,296 t) of it, followed by the south-west coast (17%, 36,017 t), the south-east coast (12%, 25,322 t) and the north-east coast (8%, 15,875 t). The von Bertalanffy’s growth equation was Lt = 143.8 [1-e–0.48 (t + 0.03285)]. Natural mortality, Exploitation ratio and Maximum Sustainable Yield (MSY) were 0.76; 0.65 and 1,59,504 t respectively. Recruitment was substantial throughout the year with a single modal peak during June-October. With lower lengths at first capture and recruitment and with exploitation above the maximum permissible level and landings higher than MSY; the species appears to be overexploited along the Indian coasts. The present study is the first holistic report on the population parameters and stock status of T. lepturus from the Indian EEZ. Keywords: Cutlass fishes, Management, Recruitment, Stock dynamics